ILLICIT OIL TRADE: IMPLICATIONS ON SECURITY AND DEVELOPMENT IN NIGERIA - Ibekwe, Emmauel Ogueri (African Journal of Social and Behavioural Sciences, 2023)
This research looked at the effect of illicit oil trade on security and development in Nigeria with a focus on the Niger Delta region. Specifically, the study aimed to examine the nature of the illicit oil trade, the impact of illicit oil trade on the security of the Niger-Delta and the impact of illicit oil trade on the development of the Niger-Delta region. Data were collected through documentary method with the use of journals, newspapers, etc. The analysis was done qualitatively with thematic analysis. This paper revealed that illicit oil activities in the Niger-Delta region has over the years posed a great challenge to the development of the region leading to loss of government revenue; facilitation of unemployment; discouragement of foreign direct investment; threat to health and food insecurity among others. Furthermore, it showed that the issue of illicit oil trade promotes insecurity in the region. This is because these armed groups engage in illegal sale of oil to maintain their militant operations. However, this research observed that illicit oil trade only promotes employment in the activities in the informal sector. The study recommended the need to address the high rate of poverty and unemployment, blockage of the international market for stolen oil; promotion/establishment of modular refinery; effective utilization of modern technology for pipeline surveillance and adequate prosecution of arrested participants in illicit oil trade.